Semiotic evaluation of the systems of signs in the Lithuanian scholastic geographical atlases - Žalalienė, Inga (Geodesy and Cartography, 2013)
The article introduces the results of semiotic evaluation of maps in the Lithuanian scholastic geographical atlases. Cartographic signs were analysed using 1 263 maps published in 17 Lithuanian scholastic geographical atlases. The chosen atlases were published by “Briedis”, “Šviesa”, “Alma littera”, “Didakta” and “Pradai” publishing houses. The research method was developed based on the M. Dumbliauskienė's methodology for evaluation of communicative quality of thematic maps (Dumbliauskienė 2000) which emphasises the semiotic aspect of evaluation. The mentioned methodology was partly transformed (the number of indices is reduced) taking into consideration the specific character of the end users of maps (young people striving for knowledge) and perception psychology. The obtained results revealed the merits and faults of geographic production used by the Lithuanian schools which will be taken into account in further research (survey of perception of cartographic signs at school using questionnaires) and in preparing recommendations for improvement of the systems of cartographic signs in the maps of scholastic geographical atlases.